Pilihan Pengobatan Sistemik pada Psoriasis - Nugroho Nitiyoso (PT Kalbe Farma Tbk., 2022)
Psoriasis adalah salah salah satu penyakit autoimun dengan prevalensi tinggi. Gejala dan tanda psoriasis sangat bervariasi mulai dari ruam kulit kecil sampai luas, nyeri sendi, bahkan komorbiditas sistemik. Pengobatan psoriasis perlu disesuaikan, serta mempertimbangkan efikasi, keamanan, dan kenyamanan pasien. Apabila pengobatan topikal tidak berhasil, dapat dipertimbangkan pengobatan sistemik. Artikel ini akan membahas kelebihan dan keterbatasan pilihan-pilihan pengobatan sistemik untuk psoriasis. Psoriasis is an autoimmune disease with a high prevalence. Symptoms and signs of psoriasis vary widely from small to extensive skin rashes, joint pain, and even systemic comorbidities. Treatment need to be tailored to each patient’s needs, also to efficacy, safety, and patient’s comfort. Systemic treatment could be considered if topical treatment is unsuccessful. This article will discuss the advantages and limitations of systemic treatment options in psoriasis.